Role of bpag1e in neoplastic progression of oral Squamous cell carcinoma derived cells. - PRATIK RAJEEV CHAUDHARI; SILVANIA EMLIT CHARLES; MILIND MURLIDHAR VAIDYA (International Journal of Pharma and Bio Sciences, 2017)
Aberrant expression of Keratin8/18 has been consistently shown in squamous cell carcinomas. Further, knockdown of K8 in oral squamous cell carcinoma (OSCC) derived cell line resulted in alterations in levels of α6β4 integrin proteins, α6β4 integrin mediated signalling, reduction in cell motility, tumorigenic potential and Fascin expression. However, how Keratin8/18 pair modulates β4 integrin downstream signalling events is still obscure. BPAG1e and Plectin anchor the keratin network to the cell surface via β4 integrin. In order to understand the role of BPAG1e in K8/18 mediated regulation of β4 integrin signalling, it was downregulated in an OSCC derived AW13516 cell line. BPAG1e knockdown resulted in alterations in α6β4 integrin mediated signalling, reduction in cell migration, cell invasion, tumorigenic potential and altered actin organization. In summary, BPAG1e promotes cell migration and neoplastic progression by modulating α6β4 integrin mediated signalling in OSCC cells and may prove useful in prognostication of human oral cancer.